Evaluasi User Experience Content Creator Youtube terhadap Tampilan Youtube Studio dan Perbandingannya dengan Iterasi Sebelumnya menggunakan UEQ dan Diary Study - Naufal Faza Rusdi; Hanifah Muslimah Az-Zahra; Aditya Rachmadi (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
YouTube is one of the most popular platforms used to share videos. One of the main components of YouTube is users who upload their videos to the YouTube platform (content creator) using a special page Creator Studio. Even so, over time the old technology used in creating Creator Studio limited YouTube to further develop it. To overcome this, YouTube developed a new page called YouTube Studio which is accompanied by a complete change of appearance for all content creators. This research was conducted to determine the comparison of the user experience of the two pages using User Experience Questionnaire (UEQ) and diary study. The UEQ comparison results show that the old page is better than the new page in almost all aspects. According to the diary study, one of the main problems with content creators comes from the separation of various information into various tabs that are difficult to access on new pages.